2017
DOI: 10.1136/jnnp-2016-314490
|View full text |Cite
|
Sign up to set email alerts
|

Complementary and alternative treatments of multiple sclerosis: a review of the evidence from 2001 to 2016

Abstract: People with multiple sclerosis (PwMS) commonly use complementary and alternative medicines (CAM), but an understanding of their efficacy is lacking. Here, we quantitatively review the class I and class II studies of treatment efficacy for multiple sclerosis from January 2001 to January 2017, in order to assess the modern evidence for CAM use. The 38 studies included in this review are divided across five CAM types (cannabis, diet, exercise, psychological approaches and other). We found little evidence to suppo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(18 citation statements)
references
References 63 publications
(56 reference statements)
1
16
0
1
Order By: Relevance
“…1 Further, medical use of cannabis is on the rise, as it has been proposed to provide some relief for pain disorders, vomiting and nausea. [2][3][4] Systematic assessment of the literature provides little guidance, with no or insufficient evidence for most pain conditions except for neuropathic pain. The evidence supporting the latter use remains unimpressive.…”
Section: Introductionmentioning
confidence: 99%
“…1 Further, medical use of cannabis is on the rise, as it has been proposed to provide some relief for pain disorders, vomiting and nausea. [2][3][4] Systematic assessment of the literature provides little guidance, with no or insufficient evidence for most pain conditions except for neuropathic pain. The evidence supporting the latter use remains unimpressive.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the lack of controlled studies, there is a partial yet confirmed association between the dosage and the efficacy of medicinal plants. 36 We conducted the current review to investigate the results of studies with animals and humans regarding the effects of medicinal plants and plant compounds on treatment of MS.…”
Section: Discussionmentioning
confidence: 99%
“…Considering the limitation of classical treatments, complementary and alternative medicines (CAM) have been suggested and some already adopted in MS therapy 10,11 . Roy Swank proposed a low saturated fat diet to treat MS around 1950 [12][13][14] and diet supplementation with organic, gluten-free and allergen-free ingredients have been beneficial to MS patients 15 .…”
Section: Openmentioning
confidence: 99%